Caspr2 autoantibodies target multiple epitopes. Issue 4 (August 2015) - Olsen, Abby L.; Lai, Yongjie; Dalmau, Josep; Scherer, Steven S.; Lancaster, Eric
Abstract : Objective: To better understand the mechanisms of autoantibodies to the axonal protein contactin-associated protein-like 2 (Caspr2) by studying their target epitopes. Methods: A plasmid for expressing Caspr2 was modified so that the various extracellular subdomains were deleted individually and in groups. Cultured cells were transfected to express these constructs and assayed by immunofluorescence staining with a commercial Caspr2 antibody and a panel of patient sera known to react with Caspr2. Western blotting was also performed. The role of glycosylation in immunogenicity was tested with tunicamycin and PNGase F treatment. Results: Patient antibodies bound to the extracellular domain of Caspr2. Neither native protein structure nor glycosylation was required for immunoreactivity. Caspr2 constructs with single or multidomain deletions were expressed on the plasma membrane. All deletion constructs were recognized by patients' sera, although reactivity was significantly reduced with deletion of the discoidin-like subdomain and strongly reduced or abolished with larger deletions of multiple N-terminal subdomains. Caspr2 with all subdomains deleted except the discoidin-like domain was still recognized by the antibodies. Conclusion: Caspr2 autoantibodies recognize multiple target epitopes in the extracellular domain of Caspr2, including one in the discoidin-like domain. Reactivity for some epitopes is not dependent on glycosylation or native protein structure.